Treatment of dermatophytoses by film-forming topical antifungal spray / Mohd Faiz Mustaffa - Mustaffa, Mohd Faiz (2016)
Dermatophytosis is a major public health problem especially in tropical countries like Malaysia. Several studies report incidence of resistance to common treatment for dermatophytosis with drugs such as terbinafine, fluconazole, and griseofulvin. Resistance arise as consequence of non-adherence with prescribed treatment regimens, repetitive use of antifungal drugs more than once in a patient's life, incidence of reabsorption or washout of drug from the skin and failure of drug to reach the stratum corneum. Currently available antifungal preparations (ointments or creams) are easily removed after application and may contribute to none cure and/or to development of resistance. This project was initiated with the intention of producing an antifungal topical drug delivery system using film-forming polymeric solutions. The research was divided into 4 main areas which are (1) preliminary studies to test antimicrobial activities and determine the cytotoxicity of selected antimicrobial drugs and natural product extracts in vitro, (2) formulation and characterization of film-forming solutions, (3) elucidate skin permeation of selected drug, (4) determine antifungal activity and safety profile of topical film forming polymeric spray. Seventy-three (73) formulations were prepared but only 6 formulations were chosen from the preformulation studies were further testing. Formulation A was superior to the other tested formulations due dries in less than 1 minute, is non-sticky and forms a transparent film on the skin.